1993
DOI: 10.1128/aem.59.11.3519-3524.1993
|View full text |Cite
|
Sign up to set email alerts
|

Direct plating procedure for enumerating Vibrio vulnificus in oysters (Crassostrea virginica)

Abstract: A procedure for enumerating and identifying Vibrio vulnificus in oysters was developed and evaluated. This method consists of growth on a direct plating medium (VVE medium) for isolating the organism from shellfish tissues, followed by biochemical tests for differentiating and identifying presumptively positive isolates. Densities of V. vulnificus are reliably obtained in 2 to 4 days, and as few as 10 culturable cells per 100 g can be identified. The procedure was evaluated by using a DNA probe technique speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In the present study the VVAP probe identified a wider range of isolates of V. oulnificus than the API 20E assay. This is in agreement with previous studies that have reported a higher specificity and sensitivity for the VVAP probe for identification of both biotypes of V. vulnlfcus (Micelli et al 1993 ;Wright et al 1993 ;Amaro et ul. 1994).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study the VVAP probe identified a wider range of isolates of V. oulnificus than the API 20E assay. This is in agreement with previous studies that have reported a higher specificity and sensitivity for the VVAP probe for identification of both biotypes of V. vulnlfcus (Micelli et al 1993 ;Wright et al 1993 ;Amaro et ul. 1994).…”
Section: Discussionsupporting
confidence: 93%
“…Direct plating remains difficult because of the large amount of natural microflora that may also grow on selective media. Micelli and others (1993) developed an alternative method for direct plaing of V. vulnificus from oyster homogenates. Using their so‐called V. vulnificus enumeration (VVE) medium that contained Oxgall, sodium cholate, sodium taurocholate, and potassium tellurite, they reported reduction of 61% to 99% of marine‐associated background microflora without adversely affecting the recovery of V. vulnificus .…”
Section: Introductionmentioning
confidence: 99%
“…. effective in identifying V. vulnificus (Oliver et al, 1992;Miceli et al, 1993), these techniques still cannot provide optimal differentiation of the pathogen from other halophilic Vibrios (Choi, 1997). From this result, it was apparent that the two-stage nested PCR procedure provided a very specific means to differentiate all V. vulnificus from other Vibrios in the natural samples where the pathogen exists together with a large background of other procaryotic and eucaryotic cells.…”
Section: Specificity Of the Nested Pcr Amplificationmentioning
confidence: 99%